Vitalitas Sastra Lisan Kayori - Yunidar Yunidar; M Asri B; Tamrin Tamrin (JENTERA: Jurnal Kajian Sastra, 2022)
Vitality of Kayori oral literature was conducted with purpose to know the vitality or the health level of Kayori oral literature. This research was planned as qualitative and quantitative research which contained study of vitality of Kayori oral literature. The qualitative data of study of vitality of Kayori oral literature was analyzed by using analyzing method which consisted of three main activities which covered (1) data reduction, (2) data display, and (3) conclusion drawing. Furthermore, the quantitative data which was gotten through questioner technique was analyzed by quantitative descriptive based on calculation of frequency and percentage. The calculation was started by calculating the frequency and percentage the respondent characteristic. The advanced calculation was calculation of frequency and percentage from each question items which was part of testing indicator of literature vitality. The respondents of this research were 30 people from several of age level, education level, and job level. The data was gotten from the observation and questionnaire. Quantitative descriptive analysis based on calculating of frequency and percentage to determine the vitality criteria of Kayori oral literature. The result to determine the vitality or the health level of Kayori oral literature was based on eight indicators that were (1) inheriting in circle of young generation, (2) proportion of Kayori speaker in population, (3) transition of Kayori realm, (4) switch of Kayori vehicle, (5) Learning Kayori in the school, (6) Government attitude, (7) Society attitude, and (8) number and quality of documentation. Based on these results, it could be stated that Kayori oral literature had in endangered condition. AbstrakVitalitas sastra lisan Kayori dilaksanakan dengan tujuan mengetahui daya hidup atau tingkat kesehatan sastra lisan Kayori. Penelitian ini berancangan kualitatif dan kuantitatif yang memuat kajian vitalitas sastra lisan Kayori. Data kualitatif kajian vitalitas sastra lisan Kayori dianalisis dengan menggunakan model analisis yang terdiri atas tiga kegiatan utama yang meliputi (1) reduksi data (data reduction), (2) penyajian data (data display), dan (3) penarikan simpulan atau verifikasi (conclution drawing). Selanjutnya, data kuantitatif yang diperoleh melalui teknik kuesioner dianalisis secara deskriptif kuantitatif berdasarkan penghitungan frekuensi dan persentase. Penghitungan diawali dengan menghitung frekuensi dan persentase karakteristik responden. Perhitungan lanjutan adalah menghitung frekuensi dan persentase setiap item pernyataan yang merupakan bagian indikator pengujian vitalitas sastra. Responden dalam kajian ini berjumlah 30 orang dari berbagai jenjang umur, pendidikan, dan pekerjaan. Data diperoleh dari hasil pengamatan dan kuesioner. Untuk menentukan kriteria vitalitas sastra lisan Kayori digunakan analisis deskriptif kuantitatif berdasarkan penghitungan frekuensi dan persentase. Hasil perhitungan untuk menentukan daya hidup atau tingkat kesehatan sastra lisan Kayori didasarkan pada delapan indikator, yaitu (1) pewarisan di kalangan generasi muda, (2) proporsi penutur Kayori dalam populasi penduduk, (3) peralihan ranah Kayori, (4) alih wahana Kayori, (5) Kayori dalam pembelajaran di sekolah, (6) sikap pemerintah terhadap Kayori, (7) sikap masyarakat terhadap Kayori, serta (8) jumlah dan kualitas dokumentasi. Berdasarkan hasil itu, dapat dikemukakan bahwa sastra lisan Kayori sudah dalam kondisi terancam punah (endangered).